Relatively Low Prevalence of Peripheral and Placental Plasmodium Infection at Delivery in Bangui, Central African Republic - Alexandre Manirakiza; Eugène Serdouma; Djibrine Djalle; Georges Soula; Remi Laganier; Nestor Madji; Methode Moyen; Alain Le Faou; Jean Delmont (Journal of Tropical Medicine)
Introduction. The aim of this study was to estimate the prevalence of malaria among women giving birth in Bangui. Association between sociodemographic characteristics of those women and malaria, as well as prevention compliance (use of intermittent preventive treatment with sulfadoxine-pyrimethamine (IPTsp) and insecticide-treated bed nets (ITNs)), was analyzed. Methods. During September 2009, a survey was conducted on 328 women who gave birth at two main maternities of Bangui. Information was obtained by standardized questionnaire about sociodemographic criteria, IPTsp, other antimalarial treatment, and use of bet nets. Smears prepared from peripheral and placental blood were analysed for malaria parasites. Findings and Discussion. Positive results were found in 2.8% of thick peripheral blood smears and in 4.0% of placental slides. A proportion of 30.5% of the women had received at least two doses of IPTsp during the current pregnancy. Only a proportion of 42.4% of this study population had ITNs. Multigravid women were less likely to use IPTsp and ITNs. However, use of IPTsp was associated with personal income and secondary or university educational status. Hence, although this relatively prevalence was observed, more efforts are needed to implement IPTsp and ITNs, taking into account sociodemographic criteria.